CONSTRUCTION OF ELEMENTARY SCHOOL SAFETY CLIMATE: THE ROLE OF IDEALIZED INFLUENCE AND INSPIRATIONAL MOTIVATION OF THE PRINCIPAL - fathimah; Ngurah Ayu Nyoman Murniati; Supandi (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
The escalation of child violence and post-disaster infrastructure damage in elementary schools demands a resilient leadership model. This study aims to analyze the implementation of the principal's Idealized Influence and Inspirational Motivation strategies in building trust and resilience within the school community. Using a qualitative case study method at SDN 2 Ketangirejo, data was collected through interviews, observations, and analysis of the 2023-2024 Education Report Card. The findings indicate that the leadership's moral example and inspirational vision successfully created a